Exploring Aripiprazole Analogs as Antipsychotic Agents: Scaffold Morphing Approach, ADMET Profile Predictions, and Molecular Docking Studies - Swain, Girija Prasad; Pal, Dipti; Gupta, Ajay Kumar; Jain, Sanmati Kumar (Current Psychopharmacology, 2025)
IntroductionNeurotransmitters (dopamine, serotonin, noradrenaline, and acetylcholine) play crucial roles in the regulation of various physiological processes. An imbalance in their levels can result in numerous neurological and psychiatric disorders, such as depression, anxiety, and schizophrenia. Numerous computational approaches enhance the efficiency of drug discovery, one of which is the design of analogs through bioisosteric replacement. Aripiprazole (APZ), a partial agonist of dopamine D2 receptors, is widely used in treating schizophrenia and bipolar disorder. However, prolonged APZ use can lead to side effects such as cardiovascular and liver toxicity. This study aims to in silico design APZ analogs with an improved pharmacological, drug-likeness, and reduced toxicity profile.MethodsAPZ analogs were generated using the MolOpt tool. Their pharmacokinetic and toxicological (ADMET) profiles were calculated using ADMETLab 3.0 online tool. Drug likeness (DL) and drug score (DS) were predicted using Osiris property explorer (PEO). Molecular docking studies were conducted against the protein (PDB ID: 7DFP) using ArgusLab 4.0.1.Results and DiscussionA total of 983 APZ analogs were generated and 83 analogs were screened for molecular docking based on ADMET properties, DL, and DS. Docking analysis revealed that key interactions with Asp114 in the target protein were preserved in several bioisosteres, indicating potential pharmacological relevance.ConclusionBased on ADMET analysis, DL scores, DS, and docking results, the APZ bioisosteres, particularly B104, B170, and C78, emerged as promising candidates for further investigation as potential antipsychotic agents. Further work is in progress in order to evaluate the potential of these analogs as antipsychotic agents.
Keywords: ADMET